2012
DOI: 10.1143/jjap.51.06fe10
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Test of Landauer's Principle at the Sub-kBT Level

Abstract: Landauer's principle connects the logical reversibility of computational operations to physical reversibility and hence to energy dissipation, with important theoretical and practical consequences. We report the first experimental test of Landauer's principle. For logically reversible operations we measure energy dissipations much less than k B T log 2, while irreversible operations dissipate much more than k B T log 2. Measurements of a logically reversible operation on a bit with energy 30 k B T yield an ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 29 publications
0
45
0
Order By: Relevance
“…Furthermore, as we are assuming an initially thermal reservoir (see equation (4)), correlations in SR would be unnatural unless the full initial state SR ρ were also thermal, but this would then require a (Hamiltonian) interaction term between S and R; see also [dRi13]. Some reported 'violations' of Landauerʼs bound [AN01,Orl12] can be explained by their not respecting the initial product state assumption (5).…”
Section: ( 5 )mentioning
confidence: 99%
“…Furthermore, as we are assuming an initially thermal reservoir (see equation (4)), correlations in SR would be unnatural unless the full initial state SR ρ were also thermal, but this would then require a (Hamiltonian) interaction term between S and R; see also [dRi13]. Some reported 'violations' of Landauerʼs bound [AN01,Orl12] can be explained by their not respecting the initial product state assumption (5).…”
Section: ( 5 )mentioning
confidence: 99%
“…The actual amount of heat dissipated due to Landauer's principle is difÀcult to calculate, but it is proportional to the signal energy used to represent the erased information [16], and Landauer's limit of l P k f per dissipated bit is only a theoretical lower bound. Recently, Landauer's principle has been experimentally veriÀed [9] and it has also been shown that it is in fact possible to manipulate data in an electronic circuit with less dissipation than Landauer's limit [25]. This conÀrms Landauer's insight and gives hope for future applications.…”
Section: Introductionmentioning
confidence: 86%
“…But if, as is often the case, there is a copy of the bit elsewhere in the circuit, it can be used to erase the information with very little heat dissipation. Dissipation of as little as E = 0.01k B T as recently been demonstrated experimentally [Boechler et al 2010;Orlov et al 2012]. Practical trade-offs in speed and circuit complexity of adiabatic CMOS have by now a substantial literature [Younis and Knight Jr. 1993;Starosel skii 2001].…”
Section: Link Between Logical and Physical Reversibilitymentioning
confidence: 95%